The differing physiology of nitrogen and tracer gas multiple-breath washout techniques - Sandhu, D; Ritchie, GAD; Robbins, PA (European Respiratory Society, 2021)
Background Multiple-breath washout techniques are increasingly being used to assess lung function. The principal statistic obtained is the lung clearance index (LCI), but values obtained for LCI using the N2-washout technique are higher than those obtained using an exogenous tracer gas such as SF6. This study explored whether the pure O2 used for the N2 washout could underlie these higher values. Methods A model of a homogenous, reciprocally-ventilated acinus was constructed. Perfusion was kept constant, and ventilation adjusted by varying the swept volume during the breathing cycle. The blood supplying the acinus had a standard mixed-venous composition. CO2 and O2 exchange between the blood and acinar gas proceeded to equilibrium. The model was initialised with either air or air plus tracer gas as the inspirate. Washouts were conducted with pure O2 for the N2 washout or with air for the tracer gas washout. Results At normal ventilation-perfusion (V/Q) ratios, the rate of washout of N2 and exogenous tracer gas was almost indistinguishable. At low V/Q, the N2 washout lagged the tracer gas washout. At very low V/Q, N2 became trapped in the acinus. Under low V/Q conditions, breathing pure O2 introduced a marked asymmetry between the inspiratory and expiratory gas flow rates that was not present when breathing air. Discussion The use of pure O2 to washout N2 increases O2 uptake in low V/Q units. This generates a background gas flow into the acinus thatopposes flow out of the acinus during expiration, and so delays the washout of N2.